The Application of Socratic Dialogue in Agentic Group Guidance: An Effective Path to Better Emotional Regulation - Mharchelya, Mharchelya; Hariko, Rezki; Ardi, Zadrian; Nurfarhanah, Nurfarhanah (International Journal of Research in Counseling and Education, 2025)
Recent research data shows that adolescents experience poor emotional conditions. This study aims to examine the effectiveness of interventions to improve students' emotional regulation at SMAN 10 Padang. The study uses a quantitative approach with a quasi-experimental design and a time series design. The research respondents were nine students of SMAN 10 Padang in the 2025/2026 academic year, selected using purposive sampling. Research data were collected using the Student Emotional Regulation Scale, which was compiled based on the Likert scale model. The data were analyzed descriptively, followed by a Wilcoxon Signed Ranks Test using SPSS 24.0 for Windows to see the changes before and after the treatment was given, and then using the N-Gain Score to determine the effectiveness of the treatment. The results showed that agentic group guidance using the Socratic dialogue technique was effective in improving adolescents' emotional regulation through a reflective approach, social support, and self-confidence reinforcement, so it can be recommended as a sustainable emotional learning strategy in schools. The test results showed that agentic group counseling using the Socratic dialogue technique had an average N-Gain of 0.64. This means that the implementation of agentic group counseling using the Socratic dialogue technique to improve students' emotional regulation at SMA Negeri 10 Padang was quite effective.